Inovasi Pelayanan Publik Di Desa Seberang Taluk Kabupaten Kuantan Singingi - Ikhsan; Syofian; Utami, Bunga Chintia (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2020)
The purpose of this research describes the innovation of public services in public information disclosure in village governance. This research method uses primary literature studies, interviews, observations, and documentation, as well as data analysis techniques using interactive models. This research found that public service innovations are carried out by the village to be done with an Incremental innovation level and done continuously without having to change or a new invention, the driving factor of innovation success in the cooperation research site, participation, commitment, flexibility, transparency and infrastructure facilities Innovation service. Research findings can be used as a reference for legal researchers, public administration, and rural economic development